Fatores críticos de sucesso para a inovação de valor no setor público - Martins, Teresa Cristina Monteiro (2020)
Innovation through technological platforms is a reality in the private sector, evidenced by the success of applications such as Airbnb, Netflix, Uber, YouTube, among others. However, it is observed that the application of this technology in the public context does not seem to achieve the same perception of value. Innovating in value in the public sector means creating a different value noticed by citizens and society and providing efficiency and cost reduction to institutions. Thus, this thesis, it argues that the potential for delivering value from platforms can be increased by assessing what citizens perceive as value through the use of new public sector technologies. The general objective of this thesis is to propose, apply and analyze a model of success critical factors for evaluating value innovation in the public sector, called in this research: ―Radar of value innovation in the public sector‖. This general objective is divided in three specific objectives, approached in three articles, which are components of the thesis. They are: (i) to deepen the concept of value innovation and to propose a theoretical model of the Value Innovation Radar in the Public Sector; (ii) to apply and validate the model in order to identify the value innovation perception by users of a Platform for ideas management (open innovation); and (iii) to apply the model to analyze the perception of value innovation among users of an academic administration and management platform used by public universities. There is a research of an applied nature, with exploratory-descriptive objectives and qualitative and quantitative approaches, supported by systematic literature review, expert review, case study (Platform for generating ideas) and multi-case study (platform or system of academic administration and management). As results, there are the proposition of the radar model, composed of 4 dimensions and 12 critical factors. They are: Openness (accessibility, usability and motivation); Quality: (usefulness, promptness and satisfaction); Efficiency: (economy, organization and satisfaction); and Effectiveness: (confidence, culture and social impact); in addition to the application and validation of the model to the use case of the ideas challenge platform and in the context of the academic management and administration platform in use at Universities. It concludes that the creation of different innovation initiatives in value and the cost in the public sector depends on the perception of what citizens and public organizations seek as advantage when using these initiatives. It also brings to a conclusion that the concept of public value and the approach of success critical factors contribute to the reach of value innovation in the public sector and allows the evaluation of innovation projects and initiatives or technologies, reaching reflections on the effectiveness of innovation initiatives.